Globalizing Higher Education: Strategic Approaches to Enhancing Quality in Universities for International Recognition - Chotib, Moch; Saihan, Saihan; Muhith, Abd; Khusnurridlo, Moh; Anwar, Moh (JURNAL AL-TANZIM, 2025)
As universities strive for global recognition, integrating internationalization and digitalization into their educational systems has become crucial. This study aims to analyze the strategies employed by the State Islamic University's Postgraduate Program to enhance educational quality and achieve international recognition. The research approach is a case study with a qualitative design involving in-depth interviews, observation, and documentation. Data analysis is done through condensation, reduction, and visualization of data, as well as verification to ensure the validity of the findings. The study results indicate that the Postgraduate Program implements a strategy of curriculum internationalization, international cooperation, and the application of digital technology to improve the quality of education. These efforts include developing a curriculum by international standards, cooperating with foreign universities, and integrating technologies such as E-learning and AI for more interactive learning. Despite the challenges of adapting technology, continuous training is a solution to improving digital skills. The implications of this study indicate that implementing internationalization and digitalization policies can increase the competitiveness of higher education.